Valor nutricional do feno de Tifton 85 em diferentes idades de corte - Wellyngton Tadeu Vilela Carvalho (2012)
The aim of this study was to evaluate the productivity and nutritive value of Tifton 85 (Cynodon spp.) hay at 27, 43, 73 and 84 days of growth through productivity and chemical composition (chapter III), in vitro semi-automatic gas production technique (chapter IV), in situ incubation technique (chapter V), intake and digestibility trial (chapter VI) and indirect calorimetry (chapter VII). In the third chapter, it was evaluated the yield and chemical composition of Tifton 85 hay (Cynodon spp.) cut at four different ages (27, 43, 73 and 84 days). It was used an entirely randomized design with five replicates and four treatments and the results were submitted to the regression model. The equation generated by the regression model for digestible dry matter yield presented a cubic trend depending on the cutting age, represented by the equation y = 0,0002x3 0,0381x2 + 2,0423x 27,756. The equations generated for crude protein, in vitro dry matter digestibility and neutral detergent fiber showed a linear trend depending on the cutting age, represented by the equations y = -0,1431x + 23,998, y = -0,2937x + 77,242, y = 0,0839x + 70,777, respectively. In the fourth chapter it was evaluated the gas fermentation kinetics associated with dry matter degradability (DMD) of Tifton 85 hay (Cynodon spp.) obtained at 27, 43, 73 and 84 days of growth using the in vitro semi-automatic gas production technique. It was used a randomized blocks in split plots experimental design and the means were compared by SNK test (P<0.05). Cumulative gas production showed no significant difference (P>0.05) between treatments for each fermentation period. At 6 hours of fermentation gas production ranged from 13.63 to 16.61 ml / g dry matter (DM), at 12 hours it ranged from 39.14 to 45.05 ml / g of DM, at 24 hours it ranged from 103.61 to 114.23 ml / g of DM, at 48 hours it ranged from 159.96 to 173.73 ml / g of DM, at 72 hours it ranged from 173.56 to 191.37 ml / g of DM and at 96 hours it ranged from 179.48 to 197.93 ml / g of DM. The dry matter degradability (DMD) values presented by hay obtained at 27 (68.30%) and 43 (67.23%) days were similar (P>0.05) and higher than the values presented by hay obtained at 73 (62.23%) and 84 (57.67%) days (P<0.05), indicating the cutting age effect on Tifton 85 hay DMD. In the fifth chapter it was determined the ruminal degradability in situ for Tifton 85 hay obtained at 27, 43, 73 and 84 days of growth. It was used a randomized blocks in split plots experimental design and means were compared by SNK test (P<0.05). At 96 hours of incubation dry matter (77.00 and 73.36%), organic matter (76.69 and 72.70%), crude protein (87.38 and 83 80%) and neutral detergent fiber (75.50 and 71.56%) ruminal degradability obtained for hay cut at 27 and 43 days were similar (P>0.05) but higher than the values presented by hay cut at 73 and 84 days (P<0.05), which were similar (P>0.05). Hay obtained at 27 and 43 days of growth showed dry matter potentially degradable fraction of 79.32 and 78.18%, respectively. The constant dry matter degradation rate (c) was higher for hay cut at 27 days. In the sixth chapter it was evaluated the intake, nitrogen balance and apparent digestibility dry matter, organic matter and crude protein, and digestibility fibrous fractions) in sheep fed Tifton 85 (Cynodon spp.) hay obtained at four different ages (27, 43, 73 and 84 days). It was used a completely randomized experimental design with five replicates (sheep) on each treatment (cutting age). There was a linear trend for dry matter apparent digestibility coefficients (y = -0.1033 x + 64.361) and crude protein (y = -0.1561 x + 79.961), and for neutral detergent fiber digestibility coefficient (y = -0.2204 x +77.408) as a function of the cutting age (P<0.05). The nitrogen balance (nitrogen retained / nitrogen ingested) was positive for all treatments, without any influence of cutting ages (P>0.05). Lignin intake showed a linear increase depending on the cutting age (P<0.05). In seventh chapter it was evaluated the bioenergetics in sheep fed Tifton 85 (Cynodon spp.) hay obtained at four different ages (27, 43, 73 and 84 days). It was used the indirect calorimetry method with 20 sheep distributed in an entirely randomized experimental design with four treatments and five replicates, and the means were submitted to regression analysis. The caloric incremet (CI) in Kcal / UTM and in % of ingested gross energy showed a linear trend depending on the cutting age, with values ranging from 25.1 to 48.2 kcal / UTM and 9.2 to 18.2%, respectively (P<0.05). The maintenance metabolizable energy utilization efficiency (km) showed a linear trend as a function of the cutting age, represented by the equation y = 0.0034x + 0.5202. The net energy values ranged from 1.22 to 1.57 Mcal / kg DM, with an average value of 1.43 Mcal / kg DM, with no significant difference between treatments (P>0.05). The CO2 production, O2 consumption and CI, showed a linear behavior as a function of the cutting age (P<0.05). The results indicate that Tifton 85 should be used for haymaking between 27 and 43 days of growth.